2019
DOI: 10.1002/jcla.23117
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis for pregnancies with or without ultrasound abnormalities in women of advanced maternal age

Abstract: Background: Chromosomal microarray analysis (CMA) has been suggested to be routinely conducted for fetuses with ultrasound abnormalities (UA), especially with ultrasound structural anomalies (USA). Whether to routinely offer CMA to women of advanced maternal age (AMA) without UA when undergoing invasive prenatal testing is inconclusive.Objective: This study aimed to evaluate the efficiency of CMA in detecting clinically significant chromosomal abnormalities in fetuses, with or without UA, of women with AMA.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…In our study, CMA results proved that the detection rate of clinically significant CNVs was 2.37% in group 1, which is higher than the 0.92% reported by Wu et al [ 14 ]. Previous research reports showed that the incremental diagnostic rate of CMA in the group of pregnant women with AMA alone ranged from 0.29% to 1.73%, as shown in Table 6 .…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…In our study, CMA results proved that the detection rate of clinically significant CNVs was 2.37% in group 1, which is higher than the 0.92% reported by Wu et al [ 14 ]. Previous research reports showed that the incremental diagnostic rate of CMA in the group of pregnant women with AMA alone ranged from 0.29% to 1.73%, as shown in Table 6 .…”
Section: Discussioncontrasting
confidence: 74%
“…However, previous studies had shown that the fetus with USG soft markers is related to an increased risk of chromosomal abnormalities. Previous studies have shown that the incremental diagnostic rate of CMA for fetuses with USG soft markers and a normal karyotype ranged from 2.60% to 4.95% ( Table 6 ) [ 7 , 9 , 14 , 16 – 24 ]. In this study, the rate was 2.0% and the lower detection rate may be caused by the types of soft markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with those reported in the literature (Table 2). [16][17][18][19][20][21] Chen et al 22,23 reported that the calculated level of trisomy mosaicism in amniocytes was higher from fluorescent in situ hybridization (FISH) analysis (using uncultured amniocytes) compared with karyotype analysis. As mentioned above, these results may reflect the poor genetic stability and elimination of cells with trisomy during long-term cell culture (required for karyotype analysis), leading to the relatively reduced levels of trisomy mosaicism from karyotype analysis.…”
Section: Discussionmentioning
confidence: 99%